Codon Preference Optimization Increases Prokaryotic Cystatin C Expression. (3rd October 2012) - Wang, Qing; Mei, Cui; Zhen, Honghua; Zhu, Jess
Abstract : Gene expression is closely related to optimal vector-host system pairing in many prokaryotes. Redesign of the human cystatin C ( cysC ) gene using the preferred codons of the prokaryotic system may significantly increase cysC expression in Escherichia coli ( E. coli ). Specifically, cysC expression may be increased by removing unstable sequences and optimizing GC content. According to E. coli expression system codon preferences, the gene sequence was optimized while the amino acid sequence was maintained. The codon-optimized cysC (co- cysC ) and wild-type cysC (wt- cysC ) were expressed by cloning the genes into a pET-30a plasmid, thus transforming the recombinant plasmid into E. coli BL21. Before and after the optimization process, the prokaryotic expression vector and host bacteria were examined for protein expression and biological activation of CysC. The recombinant proteins in the lysate of the transformed bacteria were purified using Ni 2+ -NTA resin. Recombinant protein expression increased from 10% to 46% based on total protein expression after codon optimization. Recombinant CysC purity was above 95%. The significant increase in cysC expression in E. coli expression produced by codon optimization techniques may be applicable to commercial production systems.